DESCRIBING ANXIETY EFFECTS ON PRONUNCIATION PERFORMANCE OF ESL LEARNERS - Muhammad Faizan Ul Islam; Umar Riaz; Shahid Hussain Mir (International Journal of Contemporary Issues in Social Sciences, 2024)
This research investigates the level of English language anxiety experienced by 7th-semester BS English students at the University of Kotli Azad Jammu and Kashmir, with a focus on its impact on pronunciation performance. Through a quantitative approach, data was collected using standardized questionnaires to assess anxiety levels and self-developed questionnaires to evaluate pronunciation performance. Descriptive statistics were employed to analyze the data, revealing that students face significant levels of anxiety across various language learning situations, particularly in speaking and listening contexts. Moreover, the study found a negative correlation between English language anxiety and pronunciation performance, indicating that higher levels of anxiety are associated with lower proficiency in pronunciation. The findings underscore the importance of addressing language anxiety to enhance language learning outcomes, suggesting strategies such as reducing test anxiety, creating a supportive classroom environment, and providing additional support for pronunciation improvement. These recommendations aim to alleviate anxiety-related barriers and foster a conducive learning environment for English majors at the university.